2021
DOI: 10.3390/agronomy11122458
|View full text |Cite
|
Sign up to set email alerts
|

VISmaF: Synthetic Tree for Immersive Virtual Visualization in Smart Farming. Part I: Scientific Background Review and Model Proposal

Abstract: Computer-Generated Imagery (CGI) has received increasing interest in both research and the entertainment industry. Recent advancements in computer graphics allowed researchers and companies to create large-scale virtual environments with growing resolution and complexity. Among the different applications, the generation of biological assets is a relevant task that implies challenges due to the extreme complexity associated with natural structures. An example is represented by trees, whose composition made by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…They are capable of handling a wide range of growth and development processes, from microscopic cell division to macroscopic modeling of entire plant communities ( Makowski et al. 2019 , Louarn and Song 2020 , Crimaldi et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are capable of handling a wide range of growth and development processes, from microscopic cell division to macroscopic modeling of entire plant communities ( Makowski et al. 2019 , Louarn and Song 2020 , Crimaldi et al. 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The detected structures are combined to form a tree. In a review, Crimaldi et al [8] gave an overview of the most common approaches used to generate 3D tree models, discussing both methodologies and available commercial software. He presented a study that proposes a biomathematical model for tree growth and presents a 3D output of its structure through a real-time 3Drendering environment (Unity©).…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded by emphasizing the promising results of proximal imaging in the field of agriculture. In the framework of technology and computer-generated imagery, Crimaldi et al [11] overviewed the most diffused approaches that have been adopted to develop 3D tree models using functional-structural plant models and provided arguments for the methodologies and the available commercial software. They concentrated on approaches for rendering and modeling plants, focusing on their comparability with biological models and botanical knowledge (plant morphology, development and growth, and branching expression).…”
mentioning
confidence: 99%